IMPLEMENTASI PROGRAM JAMPEHARUPAT DALAM MENINGKATKAN PELAYANAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUMEDANG - Febianti, Fepi; Irawan, Fajar; Darojatun, Muhammad; Badriah, Nurgina; Triani, Rizki; Azzahra, Shinta (JRPA - Journal of Regional Public Administration, 2024)
The purpose of this study was to determine the implementation of the four-document newborn service guarantee program, to determine the extent to which the Sumedang Regency Population and Civil Registration Office could implement the program's services. The study used qualitative research methods with data collection, observation steps, in-depth interviews and documentation. From this study, the results were obtained, namely the finding of factors that support the socialization of the four-document newborn service guarantee program, to increase public awareness, especially pregnant women, to participate in running the program. In carrying out socialization of the Sumedang Regency Population and Civil Registration Office. Overall it can be said to be quite good, but there is a problem regarding the lack of media in carrying out socialization such as the installation of baligo and banners. In addition, the lack of public awareness of the importance of population documents There were obstacles regarding the implementation of the newborn service guarantee program four documents, to determine the extent of the Sumedang Regency Population and Civil Registration Office, namely: there are in terms of socialization to midwives in Sumedang Regency who do not have accounts, Midwives who are members of the Indonesian Midwives Association (IBI) Sumedang Regency Branch as many as 1,020 people and Midwives who practice Independently as many as 490 people. This means that there are still many midwives who do not have an account to be able to excesses to the Newborn Service Guarantee Program Four Documents. Efforts to overcome obstacles include increasing resources such as increasing the number of operators and increasing socialization.